The Practice of Islamic Psychospiritual Therapy in the Treatment of Drug Addiction at Rehabilitation Centres in Malaysia - M. Saiful Amri Zainal Abidin; M. Zohdi M. Amin; Abdulloh Salaeh; W. Fatimah Zahra’ W. Yusoff; Salmah Fa’atin (Department of `Aqidah and Islamic Thought, Academy of Islamic Studies, University of Malaya, 2024)
Indexed by SCOPUS/MYCITE